Sport events’ impact and legacy on quality of life: a scoping review - Xu, Haohan; Sato, Shintaro (Frontiers in Sports and Active Living, 2025)
Research purposeThe purpose of this research was to map and evaluate the existing literature on the impacts and legacies of sport events on quality of life outcomes, identifying trends, gaps and proposing future research directions. Based on the analysis of 70 studies that examines sport events’ impact and legacies on quality of life, this scoping review aims to address three key questions: (1) What is the current state of the literature in terms of studied context and research design? (2) Which theoretical frameworks underpin the studies? (3) What are the key gaps in this research domain?Research methodThe scoping review follows the five-stage framework proposed by Arksey and O'Malley.Results and findings(1) Predominant focus on mega/large events, heavy reliance on subjective measurements; (2) frequent absence of theoretical frameworks (3) Limited understanding of the distinct psychological mechanisms across event types that underlie quality of life outcomes.